2021
DOI: 10.1007/978-3-030-86514-6_22
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Acoustic Mosquito Tagging with Bayesian Neural Networks

Abstract: Deep learning models are now widely used in decision-making applications. These models must be robust to noise and carefully map to the underlying uncertainty in the data. Standard deterministic neural networks are well known to be poor at providing reliable estimates of uncertainty and often lack the robustness that is required for real-world deployment. In this paper, we work with an application that requires accurate uncertainty estimates in addition to good predictive performance. In particular, we conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“… 7 For a recent example, residual networks (hence ResNets, 8 i.e., deep convolutional networks with residual connections every few layers for facilitating backwards propagation of the error signal for training) were shown to outperform the competition in a study on AED. 9 A ResNet similar to the winning method from the aforementioned study was also shown to be the best performer specifically for bioacoustic call detection in an extensive comparative study 10 against a non-residual deep convolutional network, 9 shallower networks of around two or three (1D or 2D) convolutional layers commonly used for AED, 11 , 12 , 13 , 14 as well as a combination of convolutional and recurrent (i.e., designed for sequential data) layers previously used for the bioacoustic detection of Bornean gibbon calls. 15 The success of the winning model of Rizos et al.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“… 7 For a recent example, residual networks (hence ResNets, 8 i.e., deep convolutional networks with residual connections every few layers for facilitating backwards propagation of the error signal for training) were shown to outperform the competition in a study on AED. 9 A ResNet similar to the winning method from the aforementioned study was also shown to be the best performer specifically for bioacoustic call detection in an extensive comparative study 10 against a non-residual deep convolutional network, 9 shallower networks of around two or three (1D or 2D) convolutional layers commonly used for AED, 11 , 12 , 13 , 14 as well as a combination of convolutional and recurrent (i.e., designed for sequential data) layers previously used for the bioacoustic detection of Bornean gibbon calls. 15 The success of the winning model of Rizos et al.…”
Section: Introductionmentioning
confidence: 94%
“…MC-based approaches comprise Bayes by backprop 45 and MC dropout, 46 and have been applied on a wide range of data domains, including audio. 13 , 47 …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that BNNs can reduce overfitting, which is especially beneficial for small datasets like the one examined in this Challenge [70]. However, since this approach does not consistently outperform the deterministic counterparts, as discussed by [71], our aim was to scrutinise the specific impact of this approach in our study. Constructing a complete BNN requires modelling the prior distribution over all model parameters, a task that can be computationally demanding [72].…”
Section: (Bayesian) Neural Networkmentioning
confidence: 99%
“…However, it has been shown that including them during training and inference is a viable approximation to a complete BNN [70,72]. Inspired by [72], we added dropout layers to various segments of the ResNet50 architecture, particularly to the BasicBlock() and Bottleneck() modules, as per the ResNet implementation from [71]. This can be interpreted as a Monte Carlo approximation to BNNs.…”
Section: (Bayesian) Neural Networkmentioning
confidence: 99%
“…B.4]. Its structure is based on prior models that have been successful in assisting domain experts for mosquito tagging [14]. As features, the baseline uses 128 log-mel spectrogram coefficients with a time window of 30 feature frames and a stride of 5 frames for training.…”
Section: Approachesmentioning
confidence: 99%